IMPLICATIONS OF ISRĀ’ILIYYĀT’S NARRATIONS ON THE CONTEMPORARY YORUBA MUSLIMS - Abubakar, Abduljelil Ballo; Abdulsalam, Daud Olalekan; Badmus, Saheed Adewale (Jurnal Diskursus Islam, 2026)
(Isrā’īliyyāt) are stories and traditions of Jewish and Christian origin that entered early Islamic writings, particularly Qur’ānic exegesis and historical narratives which have become widespread tools of Da‘wah among Yoruba Muslim preachers. Their uncritical adoption has led to doctrinal confusion, the propagation of fabricated Hadīth, and distorted interpretations of the Qur’ān. These narratives have also reinforced superstitious beliefs, misconceptions about the infallibility of prophets, and blasphemous views regarding the Prophet’s Companions, thereby weakening the (‘Aqīdah) creed of many Yoruba Muslims. This paper examines the implications of Isrā’īliyyāt narrations on the belief system, theology, and religious practices of contemporary Yoruba Muslims. The study employs analytical and historical methods to trace the origin of (Isrā’iliyyāt), and examine its implications among Yoruba Muslims. The paper finds out that the narrations have shaped Yoruba Muslims’ theological perceptions and superstitious beliefs like reincarnation (akúdáyà) and stillbirth (àbíkú) have persisted as a result of (Isrā’īliyyāt-influenced preaching. The paper argues that Islam, as a comprehensive and revealed religion, rejects falsehood, fabrication, and superstition, and that Qur’ānic exegesis must be based strictly on authentic sources and sound scholarly principles. The paper recommends that Yoruba Muslim preachers and scholars undergo proper training in Qur’ānic sciences, Hadīth, jurisprudence, and the Arabic language to ensure accurate interpretation. The paper concludes that curbing the spread of (Isrā’īliyyāt) requires renewed scholarly commitment, intellectual discipline, and adherence to authentic Islamic epistemology, so as to preserve the purity of Islamic teachings among Yoruba Muslims.